Formulation and Evaluation of Balm Stick Preparations from the Essential Oil of Eucalyptus resinifera Leaves - Ramadhan, Eka Sujisno; Wulan, Mustika Candra; Marsandah, Marsandah; Abubakar, Andi Nur Fitriani; Agustina, Ayu Safitri; Karneng, Syahdam Safitri; Yuliana, Hasri Safitri (Jurnal Beta Kimia, 2025)
Balm is one of the pharmaceutical products with an ointment base that uses essential oils as one of the ingredients in its formulation. One of the essential oils found in Indonesia is Eucalyptus resinifera essential oil. In Indonesia, the use of E. resinifera leaf essential oil in balm stick formulations has not yet been reported. The purpose of this study was to formulate and characterize a balm stick preparation from E. resinifera leaf essential oil for the development of health products. The methods used included the formulation of E. resinifera essential oil balm with four essential oil concentrations (0%, 15%, 20%, and 25%) and evaluation of the preparations through homogeneity, spreadability, adhesion, pH, and skin irritation tests. The results showed that the best formula was Formula III, containing 20% essential oil, which met the requirements for a good balm preparation based on the results of the homogeneity test (homogeneous), spreadability test (3.9 cm), adhesion test (>1 minute), pH test (4.6), and skin irritation test (no irritation observed), and was also the most preferred according to the organoleptic test.